Structural diagram of automated quality control process of silicon wafers during their surface shaping - Nevlyudov, I.; Botsman, I.; Tesliuk, S. (International Science Group, 2021)
Currently the task of finding alternative energy sources is one of the most urgent tasks not only in Ukraine, but throughout the world. In Ukraine several types of energy production from renewable sources are used, but recently, special attention is paid to solar power plants. Monocrystalline and polycrystalline silicon wafers for solar panels are used as solar cells. As solar cells for solar panels the monocrystalline and polycrystalline silicon wafers are used.
Keywords: silicon wafer; control process; surface shaping; quality control